Reconfigurable intelligent surface assist wireless channel estimation algorithm in Internet of vehicles environment - Rong ZENG; Xiao HANG (Tongxin xuebao)
Aiming at the problem that multi-user channel estimation assisted by reconfigurable intelligent surface (RIS) in the uplink Internet of vehicles environment, a location assisted compressive sensing channel estimation algorithm was proposed.Based on the location information of the communication equipment, a single RIS-assisted single-user communication model was built, and the optimal phase shift matrix was derived according to the logical relationship between the beam angle of departure (AOD) and the angle of arrival (AOA).The perception matrix was constructed and channel estimation was performed, and finally it was extended to multi-user scenarios and solved iteratively.The optimal RIS phase shift matrix was solved based on the position information obtained by the Internet of vehicles technology, which reduced the additional training overhead of the channel and further reduces the complexity of the channel estimation.Simulation results show that the proposed algorithm based on location information has high channel estimation performance.